Nascent chain-monitored remodeling of the Sec machinery for salinity adaptation of marine bacteria - Ishii, Eiji (Proc Natl Acad Sci U S A, 2015)
SecDF interacts with the SecYEG translocon in bacteria and enhances protein export in a proton-motive-force-dependent manner. Vibrio alginolyticus, a marine-estuarine bacterium, contains two SecDF paralogs, V.SecDF1 and V.SecDF2. Here, we show that the export-enhancing function of V.SecDF1 requires Na(+) instead of H(+), whereas V.SecDF2 is Na(+)-independent, presumably requiring H(+). In accord with the cation-preference difference, V.SecDF2 was only expressed under limited Na(+) concentrations whereas V.SecDF1 was constitutive. However, it is not the decreased concentration of Na(+) per se that the bacterium senses to up-regulate the V.SecDF2 expression, because marked up-regulation of the V.SecDF2 synthesis was observed irrespective of Na(+) concentrations under certain genetic/physiological conditions: (i) when the secDF1(VA) gene was deleted and (ii) whenever the Sec export machinery was inhibited. VemP (Vibrio export monitoring polypeptide), a secretory polypeptide encoded by the upstream ORF of secDF2(VA), plays the primary role in this regulation by undergoing regulated translational elongation arrest, which leads to unfolding of the Shine–Dalgarno sequence for translation of secDF2(VA). Genetic analysis of V. alginolyticus established that the VemP-mediated regulation of SecDF2 is essential for the survival of this marine bacterium in low-salinity environments. These results reveal that a class of marine bacteria exploits nascent-chain ribosome interactions to optimize their protein export pathways to propagate efficiently under different ionic environments that they face in their life cycles.